Determination of phthalate concentrations in paper-based fast food packaging available on the U.S. market. Issue 3 (4th March 2021) - Carlos, Katherine S.; de Jager, Lowri S.; Begley, Timothy H.
ABSTRACT: Phthalates are one of many chemical compounds that are used as plasticisers. Packaging can transfer plasticisers to the surfaces of foods or other materials. A recent study suggested a link between fast food consumption and increased urine phthalate metabolites even though phthalates are most commonly found in food contact materials made of PVC while fast food packaging is most commonly composed of paper and paper board. Phthalates in PVC are usually present in percent concentrations. In non-PVC food contact materials, such as paper or paperboard, the concentrations, if any, are expected to be significantly lower which can greatly impact the analytical method used for their determination. Due to the widespread use of plasticised PVC in many commercial applications, background concentrations of phthalates are a concern for trace concentration analyses and background contamination must be avoided when performing these analyses. A glassware cleaning method was developed and a solvent extraction with dichloromethane and hexane was used to extract phthalates from paper-based food packaging. The extracts were then analysed using a GC-MS/MS. The minimum reporting concentrations for the method were determined to be 0.10–0.40 µg/g depending on the phthalate investigated. Phthalate concentrations in several different non-PVC printed and unprinted packaging are presented. Of the 54 packaging samples tested, 10 samples contained no reportable concentrations of any of the 6 phthalates investigated. Of those that were reportable, all measured lower than 10 µg/g and in fact, most had concentrations less than 1 µg/g. These data demonstrate that phthalates from fast food packaging do not significantly contribute to overall consumer exposure.